2012
DOI: 10.1038/srep00857
|View full text |Cite
|
Sign up to set email alerts
|

Development of Miniaturized Walking Biological Machines

Abstract: The quest to ‘forward-engineer’ and fabricate biological machines remains a grand challenge. Towards this end, we have fabricated locomotive “bio-bots” from hydrogels and cardiomyocytes using a 3D printer. The multi-material bio-bot consisted of a ‘biological bimorph’ cantilever structure as the actuator to power the bio-bot, and a base structure to define the asymmetric shape for locomotion. The cantilever structure was seeded with a sheet of contractile cardiomyocytes. We evaluated the locomotive mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
183
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(184 citation statements)
references
References 41 publications
0
183
0
1
Order By: Relevance
“…Populations of cardiomyocytes have been used as actuators in a variety of macroscopic mechanical devices that operate at high Re, including a millimetre-scale pump 15 , autonomous or paced walkers or swimmers 16,17 , and a jellyfish 18 , all involving twodimensional films or three-dimensional structures. These larger scale devices, with millimetre to centimetre scale deformations, generate propulsion by high Re mechanisms that are not viable at the microscale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of cardiomyocytes have been used as actuators in a variety of macroscopic mechanical devices that operate at high Re, including a millimetre-scale pump 15 , autonomous or paced walkers or swimmers 16,17 , and a jellyfish 18 , all involving twodimensional films or three-dimensional structures. These larger scale devices, with millimetre to centimetre scale deformations, generate propulsion by high Re mechanisms that are not viable at the microscale.…”
Section: Resultsmentioning
confidence: 99%
“…Primary cardiomyocytes are extracted from 2-to 4-day-old Sprague-Dawley rats 16 under approved Institutional Animal Care and Use Committee protocol number 11160. The hearts are immediately transferred to ice-cold Hank's balanced salt solution after dissection.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that PEGbased hydrogels can serve as tunable skeletons for walking biohybrid robots powered by primary cardiomyocytes. [112] A non-natural skeleton geometry, fabricated via stereolithographic 3D printing, patterned with a sheet of cardiac cells is shown to crawl across a 2D substrate with a precisely defined "stick-slip" walking mechanism ( Figure 8B). …”
Section: Use Of Primary Tissue As Biohybrid Machine Componentsmentioning
confidence: 99%
“…Therefore, analyzing the contractile force, mechanical properties, and dynamic beating behavior of heart cells is of great significance for the quantitative understanding of the mechanism of heart disease and the molecular alterations that occur in diseased heart cells (3). Moreover, cardiomyocytes have been used as actuators in the development of bio-syncretic robots in recent years (4)(5)(6)(7)(8)(9) for their advantageous functional features, including spontaneous contraction, high energy conversion efficiency, and high energy density (10). Therefore, understanding the mechanical dynamics of heart cells is essential for designing, actuating, and controlling cardiomyocyte actuation-based bio-syncretic robots.…”
Section: Introductionmentioning
confidence: 99%